Maqashid Syariah Sebagai Paradigma Pengembangunan Ekonomi Islam - Ahmad Masyhadi (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2018)
The purpose of the inheritance of Shari'ah is to achieve benefit and avoid adversity in two different time dimensions, the world and the hereafter. This means that all aspects of Islamic teachings must lead to the achievement of these objectives, including economic aspects. Therefore Islamic Economics must be able to be a solution to the acute current economic problems. The logical consequence is that to compile a building of Islamic Economics it cannot be separated from the Maqashid theory as explained earlier. Islamic Maqashid occupies a very central and vital position in formulating the methodology for developing Islamic Economics. Even Syathibi himself stated that Maqashid Shari'ah was his superstition. This means that compiling usul fiqh as a methodology cannot be separated from maqashid syari'ah. This is because the theory of maqashid can deliver the mujtahid to determine the standard of benefit in accordance with Shari'ah / law Islamic economics must put maqashid syari'ah as a reference, so that the system and knowledge that are now being formulated can provide benefits and be able to be a solution to the complex and increasingly present present economic problems. The mujtahids in the field of Islamic Economics should have applied maqashid syari'ah in their analysis of the economy. Maqashid Shari'ah in its ideal plains must also have implications for the economic behavior of Muslim individuals.